Eco-Innovation and Service Activities in the Context of Sustainable Development in Romania - Irina, Rabontu Cecilia; Gabriela, Babucea Ana (European Scientific Journal, ESJ, 2018)
Eco-innovation and sustainability are two concepts that follow the same driving direction in the sense that it determines each other having as purpose a decrease of the impact way of production on the environment by increasing the resistance of nature to environmental pressures and, not least, by obtaining a use of natural resources in an efficient and responsible way. The action of all stakeholders and all economic sectors in reducing aggression on the environment are increasingly asserting more stringent if there are taken into consideration the climate change or diminishing resources and biodiversity, eco-innovation being seen as an opportunity for businesses of any kind and with any object of activity. Service activities can be the beneficiaries of eco-innovation through the emergence and development of high-tech services. But, need to be aware also of the role they play in the environmental protection, in this way exemplifying a small part of them, namely: services of research and development leading to products and innovative services, sanitation services, waste management services where ecology is already a brand presentation and we refer here to ecological tourism services, etc. All these issues can lead to increased quality of life and create new jobs, for which we intend to analyze how can influence healthy to each other two actual concepts namely service activities, innovation and ecology. We also follow to determine how eco-innovation can contribute to the development of innovative services and together can reduce the adverse environmental effects by promoting healthy development and a sustainable economy. In order to achieve the objectives proposed, we analyzed the main literature on this subject and used descriptive statistical methods for interpreted the statistical data available in the official databases. The results of this study establish the relationship between eco-innovation, services, and sustainable development on the one hand, as to identify the place of Romania in the Eco- Innovation Scoreboard - Eco-IS in the European context and the exact situation existing in Romania in relation to support services for the ecoinnovation process, on the other hand.